Effect of Production Volume on Prevention Costs, Valuation Costs, and Damaged Products in the Seafood Processing Industry - Ardiansyah; Barus Umarella (JFBA: Journal of Financial and Behavioural Accounting, 2023)
The purpose of this study was to determine the effect of production volume on prevention costs, the effect of production volume on appraisal costs, the effect of production volume on damaged products, the Effect of prevention costs on damaged products, and the effect of appraisal costs on damaged products. This type of research is quantitative. The type of research data is secondary data for 2019-2020 which consists of reports on production volume, prevention costs, appraisal fees, and damaged products. The analytical method uses the Smart Partial Least Square (SmartPLS) software 3. The results of this study indicate that production volume has a positive and significant effect on prevention costs, production volume has a positive and significant effect on appraisal costs, production volume has a positive and significant effect on damaged products, prevention costs have a negative but not significant effect on damaged products, and appraisal costs have a positive but not significant effect on damaged products. All hypotheses put forward in this study were declared accepted. The implications of the results of this study can be taken into consideration for companies by comparing data on handling costs, appraisal costs, production volume.